Life of Pi [screenplay] - Magee, David 1962-
A young Pi Patel, overcoming a cataclysmic shipwreck, finds himself stranded on a lifeboat with the last survivor, a ferocious Bengal tiger named Richard Parker
"Best adapted screenplay"--Cover
"For you consideration"--Cover
Keywords: Human-animal relationships / Drama; Ocean travel / Drama; Orphans / Drama; Storytelling / Drama; Shipwreck survival / Drama; Motion picture plays; Human-animal relationships; Ocean travel; Orphans; Shipwreck survival; Storytelling; screenplays; Drama